MRD in Venetoclax-Based Treatment for AML: Does it Really Matter? - Bernardi, Massimo; Ferrara, Felicetto; Carrabba, Matteo Giovanni; Mastaglio, Sara; Lorentino, Francesca; Vago, Luca; Ciceri, Fabio (Frontiers in Oncology, 2022)
The prognosis of newly diagnosed patients with acute myeloid leukemia (AML) is still unfavorable in the majority of cases within intermediate and mainly adverse genetic risk group, but also in a considerable fraction of favourable-risk patients, mainly due to recurrence of disease after complete remission (CR) achievement or, less frequently, primary refractoriness . Besides genetic classification at diagnosis, post-treatment prognostic factors include minimal residual disease (MRD) evaluation in patients in CR;, in most cases MRD positivity predicts hematologic relapse potentially allowing early therapeutic intervention. Currently most commonly used methods for detection of minimal residual disease are multiparameter flow cytometry and quantitative PCR, applicable to around 90% and 50% of patients, respectively. In addition, in > 90% of AML patients, molecular aberrations can be identified by next-generation sequencing (NGS), a technology that is widely used into clinical practice for the initial mutational screening at the time of diagnosis, but more anf more often also for MRD detection because its flexibility allows using almost every mutated gene as an MRD marker.Threshold levels of residual disease and correlation with outcome have been thoroughly studied and established in younger patients treated with intensive induction and consolidation chemotherapy, and after allogeneic transplantation. Yet, experience on MRD monitoring and interpretation in patients treated with low-intensity regimens including new agents is still limited. The updated armamentarium of anti-leukemic agents includes the BCL-2 inhibitor venetoclax, which demonstrated good tolerability, high response rates and prolonged overall survival when combined with hypomethylating agents or low dose cytarabine, in patients considered too old or unfit to tolerate intensive regimens. Although remissions with negative minimal residual disease clearly demonstrated to translate into improved outcomes after intensive treatments, data supporting the same evidence in patients receiving low-intensity venetoclax-based treatments are not still consolidated. We here review and discuss more recent data on the minimal residual disease interpretation and role in AML patients treated with venetoclax-based combinations.